Student Attendance Application Using FPM10A Fingerprint with Arduino at SMK Negeri 2 Luwu - Kartika Darwis, Diandra; A Karim, Sugeng; Haripuddin, Haripuddin (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to develop and evaluate a fingerprint-based student attendance application using the FPM10A sensor integrated with Arduino and a PHP–MySQL web system at SMK Negeri 2 Luwu. The research employed a Research and Development approach with a waterfall model, and the application quality was assessed based on ISO/IEC 25010 standards covering functional suitability, usability, portability, and maintainability. Data were collected through observation, interviews, questionnaires, and documentation. The results show that all designed functions were successfully implemented, achieving full functional suitability. Usability testing involving 25 teachers yielded a score of 89.8%, categorized as excellent. The application also operated successfully across multiple browsers, confirming its portability, and demonstrated consistent maintainability through simplicity and error-handling features. The novelty of this research lies in integrating FPM10A–Arduino hardware with a lightweight web application and validating it comprehensively using ISO/IEC 25010 quality characteristics within the vocational school context. The findings contribute to improving attendance efficiency and accuracy while promoting digital transformation in school administration. Future work should include biometric performance metrics (FAR, FRR, EER), mobile platform testing, and security evaluation for biometric data protection.